Land Ahoy! Guidelines for Navigating the Choppy Waters of Observation Practice. Issue 1 (2nd January 2020) - Martin, Emily Alice; Winter, Stacy; Holder, Tim
Abstract: Observation is recognized as a valued method of service delivery in professional practice. It has been credited for its capacity to not only assess and monitor client behavior but has also been linked with the development of relationships, enhancing the practitioner's contextual understanding of the sporting landscape, and identifying key stakeholders in gaining entry. Despite being an accepted and acknowledged practice, there has been limited guidance on how to implement observation effectively into sport psychology consultancy. As a result, this article provides four practical guidelines aimed toward directing and enhancing observation practice for both trainee and experienced sport psychology practitioners.